Education Budget Politics: Is It Pro-Disabilities? Case of Yogyakarta Municipality, Indonesia - Rahmat, Al Fauzi; Purnomo, Eko Priyo; Mutiarin, Dyah; Malawani, Ajree Ducol (The Center for Disability Studies and Services Brawijaya University, 2020)
This article aims to examine the education budget policy allocated for inclusive education programs, wherein providing a budget is highlights. In this context, Yogyakarta City government is submit because of its embracement unto inclusive budget post for education. This paper used a qualitative approach with document-analysis method to analyze the inclusive education budgets from 2017 to 2019. The research findings are; first, the budget allocation for inclusive education is considering to be minimal when compared to other program budget posts. In 2017, budget allocation was only 1.02%, in 2018 amounted to 1.05%, and in 2019 1.19% of six programs set out in the educational development program objectives. Second, a critical review of the budget and realization of 2017 to 2019 inclusive education program has found to be not optimal absorbed as desired achievement targets. Even so, the evaluation of budget absorption includes in the high category on performance appraisal. Third, the number of inclusive schools and the percentage of teachers according to qualifications from 2017 to 2019 has been increasing. Fourth, the budget for the education development program in 2017 to 2019 has declined. Nevertheless, more importantly, the budget heading for inclusive management education in 2017 and 2019 has increased. Therefore, this has proven that the Yogyakarta City government has committed to realize inclusive education and deserves to establish as a region that cares about inclusive education.